TALENT MANAGEMENT STRATEGY FOR PERFORMANCE MANAGEMENT PROCESS ABOUT INCREASED PERFORMANCE AND EMPLOYEE RETENTION AT PT KNAUF PLASTERBOARD INDONESIA PLANT CILEGON - Destian, Aan; Sofianty, Eva; Wibowo, Raditya; Wulandari, Riski; Khaeruman, Khaeruman (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to analyze and evaluate talent management strategies in the recruitment process and their impact on improving employee performance and retention at PT Knauf Plasterboard Indonesia Plant Cilegon. Companies must implement a cohesive and effective recruitment strategy integrated with thorough talent management practices to address the challenges posed by business competition and the demand for high-quality human resources. This study employs a qualitative research method, utilizing data collection techniques such as in-depth interviews, observations, and document analysis. The study results indicate that implementing talent management strategies that identify competency needs, potential-based selection, and structured career development significantly improve individual and team performance. Furthermore, the strategy positively influences employee retention rates by enhancing engagement and satisfaction through well-defined career progression opportunities. This research recommends that organizations persist in advancing data-driven and technology-oriented methods within their talent management processes to navigate the increasingly intricate dynamics of the labour market effectively.